Nonopsonic phagocytosis of strains of Pseudomonas aeruginosa from cystic fibrosis patients. - Speert, D P (1984)
Pseudomonas aeruginosa is the predominant respiratory pathogen in patients with cystic fibrosis, but its mechanism of persisting in pulmonary secretions is poorly understood. We observed that three nonmucoid cystic fibrosis P. aeruginosa strains were phagocytized and one strain resisted phagocytosis by human polymorphonuclear leukocytes in the absence of serum. Phagocytosis was assessed by luminol-enhanced chemiluminescence, inspection of stained smears, bactericidal assay, reduction of nitroblue tetrazolium dye, and electron microscopy. Phagocytosis, determined by visual inspection, occurred at 35 degrees C but not at 4 degrees C. Nonopsonic phagocytosis was inhibited most efficiently by D-mannose, mannose-containing saccharides, and D-fructose. Opsonin-dependent phagocytosis of P. aeruginosa and of zymosan was not markedly inhibited by mannose, suggesting different leukocyte receptors for nonopsonic and opsonic phagocytosis.